Democratic Leadership Style and Academic Supervision in Enhancing Student Learning Achievement: The Mediating Role of Teaching Quality - Neneng Tri Wulan Sari; Uli Wildan Nuryanto; Mutoharoh Mutoharoh (LANCAH: Jurnal Inovasi dan Tren, 2026)
The subpar academic performance of kids in Serang City's public primary schools served as the impetus for this study, which was thought to be related to instructional quality, academic supervision, and democratic leadership. This study used instructional quality as a mediating variable to examine the direct and indirect impacts of academic supervision and democratic leadership on student accomplishment. 200 teachers. Instructional quality also substantially mediated both effects. chosen thru purposive sampling for a quantitative explanatory survey technique, and SEM-PLS was used to evaluate the data. The findings demonstrated that academic supervision and democratic leadership had a favorable and substantial impact on instructional quality, which, in turn, had a positive and significant impact on student accomplishment. Both effects, instructional quality, also substantially mediated both effects. also substantially mediated by instructional quality. Together, the three factors accounted for 43.3% of the variation in student performance (R² = 0.433).